The Obligations of States to Cooperate under the United Nations Convention on the Law of the Sea - Kentsa, Etienne; Moyo Dongue, Arnold (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2023)
This article examines the obligation of States to cooperate under the United Nations Convention on the Law of the Sea (UNCLOS). The authors analyse all the relevant provisions of the Convention in order to determine the nature and scope of such an obligation. The obligation to cooperate thus enshrined is intricate in nature insofar as it has several facets. This intricacy is reflected in a range of duties to cooperate expressed in a variety of phrases. The latter are sometimes mandatory, sometimes hortatory. In some cases, cooperation is even optional for States Parties. Therefore, the article adopts an extensive approach to the obligation to cooperate. The latter includes the obligation to exchange information and the obligation to negotiate or consult. In this respect, the obligation to cooperate is tricky in nature. On the one hand, the obligation to exchange information is complex because it includes two mandatory sub-obligations: the obligation of publicity and the obligation to notify. On the other hand, there is an ambivalent obligation to negotiate or consult. The article further examines the semantic diversity of relevant UNCLOS provisions, the pursuit of special States’ interests and the paucity of coercive measures against States as potential hindrances to the performance of the obligation to cooperate. The authors recommend solutions to overcome such hindrances. Good faith execution, the reconciliation of State interests with community interests, and the use of countermeasures to induce compliance are respective solutions to these limitations.